Stereoselective cyclohexadienylamine synthesis through rhodium-catalysed [2+2+2] cyclotrimerization - Fujii, Kohei; Nagashima, Yuki; Shimokawa, Takumi; Kanazawa, Junichiro; Sugiyama, Haruki; Masutomi, Koji; Uekusa, Hidehiro; Uchiyama, Masanobu; Tanaka, Ken (Nature Synthesis, 2022)
Development of a multicomponent reaction giving a single product is a major goal in synthetic organic chemistry. Catalytic [2+2+2] cyclotrimerization of two distinct alkynes and an alkene with chemo-, regio-, diastereo- and enantiocontrol offers rapid access to highly valued chiral six-membered carbocycles. However, previous [2+2+2]-cyclotrimerization methods have been thwarted by low selectivity and restricted substrate scope. Here we report the rhodium-catalysed [2+2+2] cyclotrimerization of terminal alkynes, alkynoates and cis-enamides to give synthetically valuable chiral cyclohexadienylamines with broad substrate scope and excellent selectivity without the requirement for slow addition or large excesses of reagents. Experimental and theoretical mechanistic studies revealed that the three-component [2+2+2]-cyclotrimerization reaction is highly specific towards use of the cis-enamide.